Assessment and redesign of a unit on proportionality using the Didactical Suitability tool - Esqué de los ojos, Daniel (2021)
The objective of this paper is to describe and analyze the reflection made by a teacher while using the Didactical Suitability Criteria (DS) to assess and redesign a didactical unit of proportionality. The qualitative analysis points out that the assessment made by the teacher on the aforementioned unit is rather balanced, as it contemplates all the DS components. However, while weighting the different DS items used to redesign the unit, the teacher puts more emphasis on epistemic suitability, particularly, on redesigning different tasks typologies in order to explore a broader significance of proportionality, in particular, the geometric and arithmetic ones. It is concluded that this type of result can be observed in other research projects dealing with the reflection that the teacher makes when using the didactical suitability tool.